Digging deeper: the value of deep soil carbon for potential REDD+ projects in tropical forest communities in Amazonia - Strey, Simone; Boy, Jens; Strey, Robert; Welpelo, Anna; Schönenberg, Regine; Schumann, Charlotte; Guggenberger, Georg (ERDKUNDE, 2017)
The deforestation of tropical forests plays a key role in terms of carbon dioxide emissions and thus accelerates climate change. With the initiative Reducing Emissions from Deforestation and Forest Degradation (REDD+), the UN spearheaded an approach to valorize ecosystems for their sequestered organic carbon (OC) to protect them for the sake of mitigating global climate change. In Brazil, where large areas of intact forests abound, especially within the territories of indigenous people, REDD+ schemes are highly sought after but are often hard to establish due to the given uncertainties in carbon stock evaluation at greater soil depths, intercultural communication problems and power asymmetries. With permission from the Kayapo/Mekragnoti tribe, our interdisciplinary research team dug a 10.0 m soil profile under a pristine forest situated on their indigenous territory in Pará, Brazil. Our results show that by following the Land Use, Land Use Change and Forestry (LULUCF) guidelines of the United Nations Framework Convention on Climate Change (UNFCCC), focusing on the first 0.3 m of soil only captures 21 % of the total soil OC present. Furthermore, only 51 % of soil OC was stored in the first metre, while 84 % of OC was captured if the sampling depth expanded to 3.0 m. This study notes that for adequate calculation and validation of stored soil OC, at least one real measurement (i.e., the Tier 3 approach) is needed to represent OC stocks in the subsoil.